Formulation And Evaluation Of Hand Sanitizer Gel From Clove Flower Extract (Eugenia aromatica L.) - Robiatun, Robiatun Rambe; Pangondian, Aswan; Paramitha, Ratih; Zulmai Rani; Gultom, Evi Depiana (Publisher Cv. Inara, 2022)
Clove flower (Eugenia aromatica L.) is a plant from the Myrtaceae family, the compounds contained in clove flowers are flavonoids, tannins, alkaloids, and saponins that can function as antibacterial. In addition, clove flowers also function as analgesic, anti-inflammatory, antimicrobial, antiviral, antifungal, antiseptic, antispasmodic, antiemetic, stimulant, and local anesthetic. The purpose of this study was to determine does clove flower extract (Eugenia aromatica L.) could be used as a hand sanitizer gel preparation. Clove flower simplicia powder was extracted with ethanol 96% by maceration. The extract obtained was then screened for phytochemicals, then formulated in the form of a hand sanitizer gel, by adding clove flower extract to each formula with different concentrations. The clove flower extract concentrations used were 5%, 10%, and 15%. After the hand sanitizer gel preparation was formed, the clove flower extract was then tested for the stability of the gel preparation. The clove flower extract obtained was 116.4 grams of thick extract. The results of phytochemical screening of clove flower extract showed the presence of secondary metabolites, namely flavonoids, alkaloids, saponins and tannins. Based on the evaluation of the hand sanitizer gel preparation, clove extract showed that it was physically stable during storage. Based on the acceptability or liking test conducted on 20 respondents using a questionnaire sheet, the results showed that the respondents really liked the aroma of formula F3.